PERWATAKAN TOKOH DALAM NOVEL SEPATU DAHLAN KARYA KHRISNA PABICHARA DAN RELEVANSI TERHADAP PEMBELAJARAN SASTRA DI SMA: Characterization of Figures in the Novel Sepatu Dahlan by Khrisna Pabichara and Its Relevance to Literature Learning in High School - Tiaara Nurul Hidayah; Muhammad Saleh; Sakaria (Journal of Applied Linguistics and Literature, 2026)
This study aims to describe the characterisation of figures based on the Id, Ego, and Super Ego in the novel Sepatu Dahlan by Khrisna Pabichara, as well as its relevance to literature learning at the high school level. The method used in this study is qualitative description, with the novel Sepatu Dahlan as the main data source. The research data consist of the characters in the novel, collected through reading excerpts. The data analysis techniques applied include data presentation and conclusion. The results of the study show that the Id aspect includes hope, anger, mischief, stubbornness, and fierceness. The Ego aspect includes love, perseverance, helpfulness, patience, and a willingness to assist. The Super Ego aspect includes empathy, gentleness, attentiveness, and maturity